2018
DOI: 10.21037/jtd.2018.06.140
|View full text |Cite
|
Sign up to set email alerts
|

Independent factors related to preoperative acute lung injury in 130 adults undergoing Stanford type-A acute aortic dissection surgery: a single-center cross-sectional clinical study

Abstract: In adults undergoing Stanford type-A AAD surgery, the incidence of preoperative ALI was 53.8%, and age, BMI, preoperative DBP, IL-6, and PGI2/TXB2 ratio were independent factors related to the occurrence of pre-operative ALI. Trial Registration: ClinicalTrials.gov, Identifier: NCT01894334.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…This study also found that some AAD patients had renal insufficiency and cardiac insufficiency, suggesting that for these patients the dissection have implicated renal artery, leading to poor bilateral perfusion. The cardiac insufficiency might be due to the involvement of dissection at the coronary ostium, causing hemodynamic changes and affecting cardiac function as reported previously [ 36 ].…”
Section: Discussionmentioning
confidence: 64%
“…This study also found that some AAD patients had renal insufficiency and cardiac insufficiency, suggesting that for these patients the dissection have implicated renal artery, leading to poor bilateral perfusion. The cardiac insufficiency might be due to the involvement of dissection at the coronary ostium, causing hemodynamic changes and affecting cardiac function as reported previously [ 36 ].…”
Section: Discussionmentioning
confidence: 64%
“…This article is a reanalysis of data published previously [6,11]. Data analysis was performed using SPSS for windows, Version 18.0 (IBM, Armonk, NY, USA).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that indobufen had a protective effect on the kidney. Furthermore, the activity of COX-1 was significantly inhibited in the kidney tissue of the indobufen group, and the ratio of 6-keto-PGI2 to TXB2 [1618] was increased. Previous studies have suggested that a higher ratio of 6-keto-PGI2 to TXB2 can reduce renal fibrosis [19].…”
Section: Discussionmentioning
confidence: 99%